PERBANDINGAN EFEKTIVITAS PIJAT BAYI DENGAN MENGGUNAKAN MINYAK KELAPA MURNI (Virgin Coconut Oil) DENGAN MINYAK ZAITUN (Olive Oil) PADA PERTUMBUHAN BAYI UMUR 3-6 BULAN DI WILAYAH KERJA PUSKESMAS KALIBAKUNG KABUPATEN TEGAL - Arum Meiranny; Atika Zahria Arisanti; Afita Dini Sukmana (Journal of Midwifery and Health Science of Sultan Agung, 2023)
Growth is an increase in physical size and body structure or an increase in the number and size of cellsthat can be measured easily suc asbody weight. One of the efforts to increase baby growth in the form of body weightis by providing stimulation namely baby massage. Baby massage using virgin coconut oil (VCO) is one of the stimulations that helps meet the baby’s nutritional intake. Besides virgin coconut oil, olive oil is also an oil choice used in baby massage. The Purpose of this study was to determine the comparison of the effectiveness of massage using virgin coconut oil and olive oil on weight gan for infants 3-6 months in the working area of the Kalibakung Public Health Center Tegal Regency. The Research Method used was Quasy Eksperiment Non Equivalent Pre-Post Group Design. Sample selection in this study using accidental sampling technique with a total numbe of respondent 10 babies, each treatment as many as 5 babies. The Results showed that giving massage with virgin coconut oil and olive oil was effective for increasing body wheight (p< 0,05). The results of the comparison of the effectiveness of massage using virgin coconut oil and olive oil, there was no significant difference in effectiveness with value (p> 0,05).